Juridical Review of Elections Dispute Settlement in Indonesia - Akhmad Zaki Yamani; Sunardi Sunardi; Hanafi Arief (International Journal of Law, Environment, and Natural Resources, 2024)
The research on “Juridical Review of Election Dispute Resolution in Indonesia” aims to describe the mechanism of election dispute resolution in Indonesia, and analyze the current weaknesses of election dispute resolution in Indonesia. This is a normative legal research, which examines laws and regulations in an Indonesian legal system that are coherent with written legal values, especially those related to election dispute resolution in Indonesia. The results of the study state that election settlement mechanisms are important to protect the rights of citizens and help determine whether elections are truly a reflection of the will of their citizens, as well as for elections to be considered credible, voters and election contestants must have access to effective election dispute resolution mechanisms. independent, fair, accessible and effective. Weaknesses in the settlement of election disputes that have been carried out so far have not fulfilled a sense of justice because dispute resolution is carried out through the Constitutional Court based on Article 24 C paragraph (1) of the 1945 Constitution, whose authority is then elaborated in Article 10 paragraph (1) of Law (UU) Number 24 2003 concerning the Constitutional Court as amended by Law Number 8 of 2011 (UU MK). Dispute resolution through the Constitutional Court in Jakarta is felt to be very burdensome for election participants because it is not in accordance with the principle of a cheap, fast and efficient trial. Election dispute settlement, which has been carried out for a maximum of 7 (seven) days, begins with the stages of receiving reports, researching, clarifying, conducting studies, and making decisions. The very limited completion time, which is a maximum of 7 (seven) days, can create a sense of injustice for justice seekers, because this short process can lead to haste in the examination which in turn creates a feeling of insecurity.